Hypertension and DMFT: insights from the PERSIAN Guilan Cohort Study - Mohammad Samami; Farahnaz Joukar; Soheil Hassanipour; Maryam Rabiei; Amir Valaei-Barhagh; Masoome Darizin; Mohammadreza Naghipour; Fariborz Mansour-Ghanaei (BMC, 2024)
Abstract Background This study investigated the association between hypertension and oral health status, as measured by the Decayed, Missing, and Filled Teeth (DMFT) index, using data from the PERSIAN Guilan Cohort Study (PGCS). Methods A cross-sectional analysis was conducted on 10,520 participants aged 35-70 from Guilan Province, Northern Iran. Blood pressure measurements, oral examinations, and comprehensive data collection on demographic, lifestyle, and clinical factors were performed. The DMFT index was used to assess oral health status. Statistical analyses included Pearson correlation, t-tests, and multiple linear regression. Results The mean DMFT score was significantly higher in hypertensive participants than in non-hypertensive individuals (15.80 vs. 13.62, p < 0.001). Factors associated with increased DMFT scores in both hypertensive and non-hypertensive groups included older age, lower education levels, lower BMI, not flossing, smoking, alcohol use, and infrequent tooth brushing. In the hypertensive group, urban residency was additionally associated with higher DMFT scores. For non-hypertensive participants, hookah use, not using mouthwash, and lower socioeconomic status were also linked to increased DMFT scores. A significant negative correlation was found between blood triglyceride levels and DMFT scores in individuals with hypertension (p = 0.037). Conclusion This study establishes a significant association between hypertension and poor oral health, as evidenced by elevated DMFT scores. The findings highlight the importance of integrated healthcare approaches that consider cardiovascular and oral health.